Neuropsychiatric effects of neurodegeneration of the medial versus lateral ventral prefrontal cortex in humans. (December 2015) - Huey, Edward D.; Lee, Seonjoo; Brickman, Adam M.; Manoochehri, Masood; Griffith, Erica; Devanand, D.P.; Stern, Yaakov; Grafman, Jordan
Abstract: Animal evidence suggests that a brain network involving the medial and rostral ventral prefrontal cortex (PFC) is central for threat response and arousal and a network involving the lateral and caudal PFC plays an important role in reward learning and behavioral control. In this study, we contrasted the neuropsychiatric effects of degeneration of the medial versus lateral PFC in 43 patients with Frontotemporal dementia (FTD) and 11 patients with Corticobasal Syndrome (CBS) using MRI, the Neuropsychiatric Inventory (NPI), and the Sorting, Tower, Twenty Questions, and Fluency tests of the Delis-Kaplan Executive Function System (D-KEFS). Deviations in MRI grey matter volume from 86 age-matched healthy control subjects were determined for the patients using FreeSurfer. Multivariate regression was used to determine which brain areas were associated with specific neuropsychiatric and cognitive symptoms. Decreased grey matter volume of the right medial ventral PFC was associated with increased anxiety and apathy, decreased volume of the right lateral ventral PFC with apathy and inappropriate repetitive behaviors, and of the left lateral ventral PFC with poor performance on the sorting and Twenty Questions task in patients with FTD and CBS. Similar to in animal studies, damage to the medial OFC appears to be associated with a disruption of arousal, and damage to the lateral OFC appears to be associated with deficits in trial-and-error learning and behavioral dysregulation. Studies of brain dysfunction in humans are valuable to bridge animal and human neuropsychiatric research.